Karakterisasi Protein Spesifik Aeromonas hydrophila Penyebab Penyakit Ulser pada Ikan Mas - Aksono Herupradoto, Bimo; Atik Yuliani, Gandul (Jurnal Veteriner; Vol 11 No 3 (2010), 2010)
The aim of this research is to find antigenic protein of Aeromonas hidrophyla (S-layer) local isolateswhich can be used as a material diagnostic reagent and to produce monoclonal antibody as a kit diagnosticfor ulcer disease and red sore disease. Aeromonas hydrophila were isolated from gold fish (Cyprinus CarpioLinn) that were got from Balai Budidaya Ikan Punten, Batu, East Java. Identification were done usingbiochemical test and were cultured on specific media called TSA. Protein characterized were analyzedthrough some stages: creating antigen homogenate, determining antigen homogenate concentration, andprotein characterizing using SDS-PAGE. Result showed that Aeromonas hydrophila protein molecularweight 174,2 kDa; 164,4 kDa; 101,4 kDa; 83,8 kDa; 71,4 kDa; 68,4 kDa; 61,7 kDa; 58,1 kDa; 53,7 kDa; 50,1kDa; 46,1 kDa; 41,5 kDa; 39,0 kDa; 35,2 kDa; 28,4 kDa; 22,2 kDa. Aeromonas hidrophylla s-layer proteinmolecular weight 53 kDa and 61 kDa had immunogenic trait. Thus, it can be concluded that the proteincan be developed potentially as a diagnostic reagent.
Keywords: Aeromonas hydrophila, ulcer disease, gold fish.